Metabolic adaptation of glucose-deprived macrophages involves partial gluconeogenesis - Katharina Schindlmaier; Theresa Haitzmann; Visnja Bubalo; Barbara Konrad; Joseph Jelwan; Gabriele Bluemel; Sonja Rittchen; Vanessa Jäger; Michael A. Dengler; Luka Brcic; Jörg Lindenmann; Leigh M. Marsh; et al. (Proceedings of the National Academy of Sciences, 2025)
Macrophages are recruited to sites of infection contributing to the killing of bacteria, but also to malignant tumors, where they promote angiogenesis and suppress antitumor immune responses. The metabolic microenvironment in tumors is frequently depleted of important nutrients such as glucose. Here, we investigated metabolic adaptation strategies of macrophages to glucose deprivation using stable isotopic tracing. Lactate production was decreased, potentially indicating a reduction of glycolysis. In contrast, the contribution of glutamine to the tricarboxylic acid cycle via α-ketoglutarate and reductive carboxylation were increased. Moreover, gluconeogenesis, the reverse pathway of glycolysis, was activated in glucose-deprived macrophages, proceeding partially to the generation of glycolytic intermediates and glycerol-3-phosphate. The partial gluconeogenesis pathway was abrogated in human and murine macrophages lacking the initial gluconeogenic enzyme phosphoenolpyruvate carboxykinase (PCK2, mitochondrial isoform). Partial gluconeogenesis was higher in anti-inflammatory, interleukin-4-stimulated compared to proinflammatory, interferon-γ/lipopolysaccharide-stimulated macrophages. Single-cell analysis and immunostaining revealed expression of PCK2 in macrophages from both lung cancer and normal lung. Low glucose conditions only partially modulated macrophage phenotypes, leading to reduced CD80 surface marker levels in proinflammatory, and enhanced vascular endothelial growth factor expression in anti-inflammatory macrophages. Our study reveals partial gluconeogenesis in glucose-deprived macrophages and shows that this versatile type of immune cells exhibits remarkable metabolic flexibility.